Immune Checkpoints: Novel Therapeutic Targets to Attenuate Sepsis-Induced Immunosuppression - McBride, Margaret A.; Patil, Tazeen K.; Bohannon, Julia K.; Hernandez, Antonio; Sherwood, Edward R.; Patil, Naeem K. (Frontiers in Immunology, 2021)
Sepsis is a leading cause of death in intensive care units and survivors develop prolonged immunosuppression and a high incidence of recurrent infections. No definitive therapy exists to treat sepsis and physicians rely on supportive care including antibiotics, intravenous fluids, and vasopressors. With the rising incidence of antibiotic resistant microbes, it is becoming increasingly critical to discover novel therapeutics. Sepsis-induced leukocyte dysfunction and immunosuppression is recognized as an important contributor towards increased morbidity and mortality. Pre-clinical and clinical studies show that specific cell surface inhibitory immune checkpoint receptors and ligands including PD-1, PD-L1, CTLA4, BTLA, TIM3, OX40, and 2B4 play important roles in the pathophysiology of sepsis by mediating a fine balance between host immune competency and immunosuppression. Pre-clinical studies targeting the inhibitory effects of these immune checkpoints have demonstrated reversal of leukocyte dysfunction and improved host resistance of infection. Measurement of immune checkpoint expression on peripheral blood leukocytes may serve as a means of stratifying patients to direct individualized therapy. This review focuses on advances in our understanding of the role of immune checkpoints in the host response to infections, and the potential clinical application of therapeutics targeting the inhibitory immune checkpoint pathways for the management of septic patients.